2008
DOI: 10.1519/jsc.0b013e31818746fe
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Alterations Due to Different Loading Schemes in Early Acceleration Sprint Performance From Starting Blocks

Abstract: The purpose of this study was to examine the changes to block start and early acceleration sprint kinematics with resisted sled towing. Ten male sprinters performed 12 sprints (four each of unresisted and approximately 10 and 20% body mass [BM]) for 10 m from a block start. Two-dimensional high-speed video footage (250 Hz) of the starting action and the first three steps of each sprint were recorded to enable the sagittal sprinting kinematic parameters to be obtained using APAS motion analysis software. The ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 10 publications
7
65
2
3
Order By: Relevance
“…Because of this more pronounced horizontal force production, also the angle of force production (angle of FP) was smaller (more horizontal) during the 6 th step and also during the 2 nd step in Sled20. The results of the present study (longer performance time, FPT, and smaller step frequency and angle of FP) support the findings of the earlier studies (Maulder et al 2008 andLockie et al 2003). It can be suggested that sled-pulling is a good exercise (especially during later steps of 10 m start), if the aim is to develop horizontal force production and that heavier sled-pulling (Sled20 in the present study) might be more efficient in this aspect.…”
Section: Sled-pulling Vs Block Startsupporting
confidence: 89%
See 3 more Smart Citations
“…Because of this more pronounced horizontal force production, also the angle of force production (angle of FP) was smaller (more horizontal) during the 6 th step and also during the 2 nd step in Sled20. The results of the present study (longer performance time, FPT, and smaller step frequency and angle of FP) support the findings of the earlier studies (Maulder et al 2008 andLockie et al 2003). It can be suggested that sled-pulling is a good exercise (especially during later steps of 10 m start), if the aim is to develop horizontal force production and that heavier sled-pulling (Sled20 in the present study) might be more efficient in this aspect.…”
Section: Sled-pulling Vs Block Startsupporting
confidence: 89%
“…There has been only a few studies comparing biomechanics of sprinting and strength exercises: sprint start vs. sled-pulling (Maulder et al 2008 andLockie et al 2003) and maximum speed sprinting vs. forward bounding exercises (Mero & Komi 1994). …”
Section: Biomechanical Comparison Between Sprint Start and Selected Smentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of sled training as part of strength and power training regimes is now common practice with various sports integrating its use for improvements in speed which is well documented in the literature [1,2]. Although initial research has focused upon the benefits of sled training on improving speed [1], subsequent studies have investigated the optimal load [3][4][5], biomechanical analyses of sprinting kinematics (technique, stride length, contact time) [6,7] and establishing coefficients of friction to determine the amount of work performed during the activity [8]. These studies have primarily focused upon sled pulling, whereas investigations into sled pushing are quite limited and have focused upon either bob-skeleton athletes [9], strongman athletes [10] or EMG muscle activation [11].…”
mentioning
confidence: 99%